Diabetes mellitus activates fetal gene program and intensifies cardiac remodeling and oxidative stress in aged spontaneously hypertensive rats - Rosa, Camila Moreno [UNESP]; Xavier, Natasha Priscilla [UNESP]; Campos, Dijon Henrique [UNESP]; Fernandes, Ana Angelica Henrique [UNESP]; Mariano Cezar, Marcelo Diarcadia [UNESP]; Martinez, Paula Felippe [UNESP]; Cicogna, Antonio Carlos [UNESP]; Gimenes, Camila [UNESP]; Gimenes, Rodrigo [UNESP]; Okoshi, Marina Politi [UNESP]; Okoshi, Katashi [UNESP] (Biomed Central Ltd., 2013)
Background: The combination of systemic arterial hypertension and diabetes mellitus (DM) induces greater cardiac remodeling than either condition alone. However, this association has been poorly addressed in senescent rats. Therefore, this study aimed to analyze the influence of streptozotocin-induced DM on ventricular remodeling and oxidative stress in aged spontaneously hypertensive rats (SHR).Methods: Fifty 18 month old male SHR were divided into two groups: control (SHR, n = 25) and diabetic (SHR-DM, n = 25). DM was induced by streptozotocin (40 mg/kg, i.p.). After nine weeks, the rats underwent echocardiography and myocardial functional study in left ventricular (LV) isolated papillary muscle preparations. LV samples were obtained to measure myocyte diameters, interstitial collagen fraction, and hydroxyproline concentration. Gene expression of atrial natriuretic peptide (ANP) and alpha- and beta-myosin heavy chain (MyHC) isoforms was evaluated by RT-PCR. Serum oxidative stress was assessed by measuring lipid hydroperoxide concentration and superoxide dismutase and glutathione peroxidase activities. Statistics: Student's t test or Mann-Whitney test, p < 0.05.Results: SHR-DM presented higher blood glucose (487 +/- 29 vs. 89.1 +/- 21.1 mg/dL) and lower body weight (277 +/- 26 vs. 339 +/- 38 g). Systolic blood pressure did not differ between groups. Echocardiography showed LV and left atrial dilation, LV diastolic and relative wall thickness decrease, and LV systolic and diastolic function impairment in SHR-DM. Papillary muscle study showed decreased myocardial contractility and contractile reserve in SHR-DM. Myocyte diameters and myocardial interstitial collagen fraction and hydroxyproline concentration did not differ between groups. Increased serum pro-oxidant activity and gene expression of ANP and beta/alpha-MyHC ratio were observed in DM.Conclusion: Diabetes mellitus induces cardiac dilation and functional impairment, increases oxidative stress and activates fetal gene program in aged spontaneously hypertensive rats.
Keywords: Diabetes mellitus; Oxidative stress; Systemic hypertension; Spontaneously hypertensive rats; Elderly